Regulation of electron and proton transfer by the protein matrix of cytochrome C oxidase - Farantos, Stavros C.; Guallar, Victor; Varotsis, Constantinos; Daskalakis, Vangelis; Farantos, Stavros C. (My University, 2011)
Cytochrome c oxidase (CcO) catalyzes the four-electron reduction of molecular oxygen to water and couples this reduction to the pumping of four protons through the protein matrix. Water molecules inside the protein are involved in the proton pumping activity as proton carriers. A highly conserved water molecule, among different CcO enzymes, lies between the heme a 3 propionates. Here, we show, by quantum mechanical/molecular mechanical (QM/MM) simulations, that this conserved water molecule can transfer its proton to propionate-A. His403 residue coordinates to the Mg site near the so-called water pool. By both QM/MM and molecular dynamics calculations, we demonstrate that the also conserved His403 residue, adjacent to the heme a 3 propionate-A, plays a role of a valve controlling the protonation state of the propionate-A/Asp399 pair. This, in turn, controls the oxidation state of the heme a 3 iron, linking in this way, the D-proton pathway to the water pool
Keywords: Electron Transport Complex IV; Heme; Heme a3